The impact of postpartum depression on maternal responsiveness in infant care - LI Shuzhen; WANG Fang; WANG Ke; LIU Su; WEI Qian; YANG Qing; LIU Leilei; SHI Huijing (Shanghai yufang yixue)
ObjectiveTo analyze the impact of maternal postpartum depression (PPD) at 2 months postpartum on caregiving for infants aged 2 to 24 months, and to provide a scientific basis for future maternal and infant healthcare services.MethodsBased on the Shanghai Maternal-Child Pairs Cohort, 1 060 mother-child pairs were selected from those fully participating in follow-up visits at 2, 6, 12, and 24 months postpartum. Pregnancy and childbirth-related information was collected using standardized questionnaire surveys and hospital obstetric and maternity records. The Edinburgh postpartum depression scale was used to assess the maternal postpartum depressive symptoms at 2 months postpartum. At 2, 6, 12, and 24 months postpartum, questionnaire survey was used to evaluate the maternal responsiveness in caregiving and the provision of early learning opportunities for infants. Scores for responsive caregiving and early learning opportunities at 2, 6, 12, and 24 months were grouped based on the 25th percentile (P25) of total scores. The mixed-effects model was used to analyze the longitudinal impact of maternal postpartum depression at 2 months on the caregiving of 2 to 24-month-old infants.ResultsThe longitudinal results from the mixed-effects model did not show an impact of maternal PPD on infant responsive caregiving within 12 months and early learning opportunities within 24 months. However, cross-sectional analysis revealed that, compared to the non-PPD group, the risk of low responsive caregiving at 2 months in the PPD group was 93% higher (OR=1.931, 95%CI: 1.113‒3.364, P=0.019). The risks for low provision of early learning opportunities at 2 months and 24 months increased by 59% (OR=1.589, 95%CI: 1.082‒2.324, P=0.017) and 60% (OR=1.598, 95%CI:1.120‒2.279, P=0.010), respectively.ConclusionMaternal postpartum depression increases the risk of low responsive caregiving at 2 months, but its long-term effects warrant further research.